2021
DOI: 10.7150/thno.56383
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Gαi1 and Gαi3 in interleukin-4-induced signaling, macrophage M2 polarization and allergic asthma response

Abstract: IL-4 induces Akt activation in macrophages, required for full M2 (alternative) polarization. We examined the roles of Gαi1 and Gαi3 in M2 polarization using multiple genetic methods. Methods and Results: In MEFs and primary murine BMDMs, Gαi1/3 shRNA, knockout or dominant negative mutations attenuated IL-4-induced IL4Rα endocytosis, Gab1 recruitment as well as Akt activation, leaving STAT6 signaling unaffected. Following IL-4 stimulation, Gαi1/3 proteins associated with the intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…The cell line has previously been tested and authenticated by the Cell Bank of Shanghai Biological Institution. Wild-type (WT), Gαi1 and Gαi3 double knockout (DKO), Gαi1, Gαi2 or Gαi3 single knockout (SKO) mouse embryonic fibroblasts (MEFs), as well as WT and Gab1 KO MEFs, were cultivated as previously described 25 , 27 - 30 . Cells were starved in 0.5% FBS medium overnight plus 30 min warm PBS for signaling analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The cell line has previously been tested and authenticated by the Cell Bank of Shanghai Biological Institution. Wild-type (WT), Gαi1 and Gαi3 double knockout (DKO), Gαi1, Gαi2 or Gαi3 single knockout (SKO) mouse embryonic fibroblasts (MEFs), as well as WT and Gab1 KO MEFs, were cultivated as previously described 25 , 27 - 30 . Cells were starved in 0.5% FBS medium overnight plus 30 min warm PBS for signaling analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed protocols for qPCR were previously described. 18 The qPCR was performed by the SYBR Premix Ex TaqTM kit under the ABI-7500 PCR system (Shanghai, China). 13 mRNA expression was quantified by 2 −ΔΔCt protocol with glyceraldehyde-3-phosphatedehydrogenase (GAPDH) as the internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Next, a previously-described CRISPR/Cas9-Gαi3-KO-puro construct 15 , 16 was transduced to the Cas9-expressing pOS-1 primary cells. Thereafter, single stable pOS-1 cells with the Gαi3 KO construct, or the ko-Gαi3 cells, were established after Gαi3 KO screening, and Gαi3 mRNA and protein (Figure 4A ) depletion was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has identified an essential role of Gαi proteins in transducing signals for multiple RTKs [14][15][16][17][18][19][20]. We found that EGFR-induced Akt-mTOR activation was abolished after Gαi1/3 double knockout (DKO) or silencing [20].…”
Section: Introductionmentioning
confidence: 99%